The effect of theoretical and student-centered interactive education on intern nursing students’ knowledge and consideration regarding human papillomavirus and its vaccine in Turkey: A repeated measures design - Serap Açıkgöz; İlknur Göl (Belitung Raya Foundation, Indonesia, 2023)
Background: Intern nursing students not only belong to the high-risk group for human papillomavirus (HPV) infection and its associated complications but also represent the future healthcare workforce. Therefore, they constitute a significant group that should comprehensively understand HPV and its vaccine. Objective: This study aimed to assess the impact of educational interventions on intern nursing students’ knowledge and considerations related to HPV and its vaccine. Methods: A repeated measures design with pretest/posttest measures was employed. The study involved 88 students at a university in Turkey and was conducted between November 2021 and February 2022. Data were collected using a Personal Information Form and the HPV Information Scale. All participants received theoretical and student-centered interactive education, and data were analyzed using numerical data, percentage distributions, Bonferroni correction, and one-way repeated measures ANOVA. Results: The total score of the scale and the scores of all four sub-dimensions obtained in the first and third months after the education were significantly higher than those obtained before the education (p <0.001). Additionally, the proportion of students considering getting an HPV vaccine increased following the education (p <0.001). Conclusions: The education on HPV and its vaccine potentially improved students’ knowledge levels and increased consideration for vaccination. Implementing interventions that equip nursing students with sufficient knowledge about HPV and its vaccine can contribute to reducing HPV-related cancer rates. Therefore, it is recommended to implement educational programs focused on the prevention of HPV-related cancers.